ASSESSMENT OF ANTI-NOCICEPTIVE EFFICACY OF COSTUS SPECIOSUS RHIZOME IN SWISS ALBINO MICE - Upendra Nagaich; Sanjib Bhattacharya (Wolters Kluwer Medknow Publications, 2010)
Present study attempts to evaluate the anti-nociceptive activity of the aqueous andethanol extracts of Costus speciosus rhizome (CPA and CPE) in Swiss albino mice. Themaceration extracts were evaluated for anti-nociceptive activity by acetic acid-inducedwrithing and tail flick method in mice. The anti-nociceptive screening revealedsignificant peripheral anti-nociceptive actions of both extracts against acetic acid inducedwrithing in mice. Aqueous extract (CPA) significantly inhibited writhes at the dose of 75and 150 mg/kg body weight, while ethanol extract (CPE) produced significant protectionat the dose of 150 mg/kg body weight. However, in tail flick method only the ethanolextract (CPE) showed significant central analgesic action, while aqueous extract wastotally ineffective. The present investigation demonstrates that the rhizome extracts of C.speciosus exhibited significant anti-nociceptive effects in Swiss albino mice.